Improving the maritime transshipment operations at the Noble Group - FRAGKOS I. (Institutional Knowledge at Singapore Management University, 2016)
The Noble Group is a market-leading global supply chain manager of agricultural products, metals, and minerals, operating in more than 140 locations. This paper focuses on Noble’s maritime operations in Indonesia, where coal is transported from mines to ocean-bound vessels via roads and rivers. Currently, transportation delays are causing Noble to lose tens of millions of dollars per year in demurrage and detention penalties. Although the company can hire additional resources (such as barges and floating cranes) in advance to minimize the impact of delays, the economic benefit of doing so is often unclear. To reduce or eliminate these delays, we develop a modeling framework and decision support system to facilitate the planning and management of Noble’s transshipment operations. The system utilizes fast search algorithms that deliver efficient schedules, minimizing the cost of delays and additional resources required, and resulting in monthly savings exceeding $1 million.